Learning environment and the development of student's generic skills - Rahman, Saemah; Mokhtar, Seri Bunian; Mohamad Yassin, Ruhizan; Jusoff, Kamaruzaman; Mohd Hamzah, Mohd Izham (IDOSI Publications, 2011)
This study aimed to identify the influence of learning environment on the development of student's generic skills in technical institution. The research instrument consists of 16 constructs measuring six scales of learning environment and ten scales to measure student's generic skills. The instrument was administered to 147 engineering students in one polytechnic in Malaysia. Result of multiple-regression analysis showed significant contribution of four learning environment factors to the variation of generic skills among the respondents. Clarity of the program objective is the most significant predictor to the development of generic skills in this study followed by the assessment, teaching approach and, community of learning. Examining aspects that contribute to the development of student's generic skills in these four elements is important in designing a curriculum that support and promote the development of generic skills among students.